Special anti-dimpling mold material for large gas turbine casing forming and its preparation method
Patent Information
- Application Number
- CN202611213870.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-11
AI Technical Summary
这类方式在一般结构件中可取得一定效果,但用于大型厚壁机匣时,往往仍存在几个方面的不足:其一,若采用无机填料、玻璃微珠、碳质导热填料等功能组分,虽然可能改善局部收缩或散热条件,但该类组分通常不属于可完全烧失的有机组分,容易受到模料灰分指标限制;其二,单纯依赖可烧失有机填料降低收缩,容易使体系黏度升高、复杂部位充填受限,并可能对表面复制质量产生影响;其三,模料在液-固转变区间的状态若缺乏适当调节,即使整体收缩率有所下降,厚壁区域内部后续收缩对已初步定型表层的影响仍可能较明显;其四,高填充全有机模料体系在保温、脱泡和重复使用过程中还可能出现分层或均匀性下降,进而影响批次稳定性和成型一致性
本申请并非采用单一的体积补偿思路,而是将全有机晶化流变复合调节剂(改善有机支撑组分分布稳定性并可能调节半固态阶段形态稳定性)与级配低收缩有机填充相(精细体积占位)在连续相中配合使用。该体系有助于提高全有机高填充体系在液-固转变区间的半固态稳定性,并通过细尺度支撑和级配体积占位方式补偿部分收缩,从而降低中心部位后收缩向先行固化表层集中传递的倾向,降低了局部凹陷倾向。
Smart Images

Figure CN122702933B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of non-metallic organic molding materials and wax-based molding materials for investment casting, and relates to anti-denting special molding materials for forming large gas turbine casings and their preparation methods. Background Technology
[0002] In investment casting, wax-based molding materials are non-metallic organic molding materials used to construct the shape of the casting wax model. They not only shape the casting but also influence dimensional transfer, surface replication, and subsequent shell quality. For components like large gas turbine casings, which have large structural dimensions, significant wall thickness variations, and numerous ribs and transition areas, the molding material typically faces more complex thermal processes and volume changes during injection, cooling, and demolding. Especially in thick-walled areas, the cooling rates between the interior and surface of the molding material often differ. After the surface hardens first, the interior continues to undergo phase transformation and volume shrinkage, easily creating a traction effect that transfers from the center to the surface. This can lead to problems such as localized depressions, contour fluctuations, or increased trimming allowances. This problem is more pronounced in large casing-type components due to their more complex thickness variations and heat transfer paths, making it difficult to achieve consistent molding across all parts using conventional non-metallic wax-based molding material systems. In addition, the ash content of investment casting mold materials is also limited during the dewaxing and calcination process. Especially when used for high-precision large casing wax molds, it is usually desirable for the mold material components to be fully burned off in order to reduce the impact of residual ash on the shell and casting quality.
[0003] Existing molding compound systems typically improve molding stability by adjusting the paraffin-to-resin ratio, increasing filler content, or adding common thermally conductive components. While these methods are effective for general structural parts, they often have several shortcomings when used in large, thick-walled casings: First, while using functional components such as inorganic fillers, glass microspheres, and carbonaceous thermally conductive fillers may improve local shrinkage or heat dissipation, these components are usually not completely burnable organic components and are easily limited by the ash content of the molding compound. Second, relying solely on burnable organic fillers to reduce shrinkage can easily increase system viscosity, restrict filling in complex areas, and potentially affect surface replication quality. Third, if the state of the molding compound in the liquid-solid transition zone is not properly adjusted, even if the overall shrinkage rate decreases, subsequent shrinkage in thick-walled areas may still have a significant impact on the initially shaped surface layer. Fourth, highly filled, all-organic molding compound systems may experience delamination or decreased uniformity during heat preservation, degassing, and reuse, thus affecting batch stability and molding consistency.
[0004] Therefore, for non-metallic wax-based molding materials used in the molding of large gas turbine casings, in addition to meeting basic flowability and moldability requirements, it is also necessary to balance semi-solid stability during the liquid-solid transition stage, volume compensation, and dispersion stability under high-filling conditions, while adhering to the constraints of low ash content and fully organic flammable formulations. It remains necessary to provide a special anti-denting molding material and its preparation method suitable for the molding of large gas turbine casings, in order to improve the tendency for localized denting in thick-walled areas and enhance the uniformity and adaptability of the molding material system during actual processing. Summary of the Invention
[0005] To address the aforementioned problems, the present invention aims to provide a special anti-denting molding compound for molding large gas turbine casings and its preparation method. This molding compound addresses the problem of localized denting that easily occurs in the thick-walled areas of large casings during molding and cooling. By introducing a fully organic crystallized rheology composite modifier, a graded low-shrinkage organic filler phase, and an anti-delamination stabilizer into the wax-resin continuous phase, it helps improve the semi-solid stability and volume shrinkage transfer state of the fully organic high-filler system during the liquid-solid transition stage. The preparation method employs a composite modifier pre-preparation, segmented dispersion, and batch feeding process, which helps improve the interfacial wetting stability and component distribution uniformity of the high-filler system. This molding compound is a non-metallic organic composite molding material used for wax molding of complex large components. It can reduce the tendency for localized denting in thick-walled areas due to asynchronous internal and external cooling while meeting low ash content requirements, and also takes into account the molding adaptability, surface replication ability, and processing stability of complex parts.
[0006] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a special anti-denting molding compound for forming large gas turbine casings, the method comprising: S1: Vacuum drying of the first low-ash organic support micro powder yields pretreated organic support micro powder; the pretreated organic support micro powder, polyethylene wax, and maleic anhydride-grafted polyethylene wax are added to a high-shear mixing vessel; after heating, shearing and mixing are performed at the first rotation speed; after mixing, the material is spread in a thin layer on a stainless steel tray, pressed and solidified by cooling rollers, and then frozen, pulverized, and sieved to obtain a fully organic crystallized rheology composite modifier. S2: Add the base wax phase into the wax melting kettle and stir to melt it; add the resin reinforcing phase, heat up and mechanically stir at the second speed to obtain a continuous wax-resin phase; S3: Add an all-organic crystallization rheology modifier, an anti-stratification stabilizer and antioxidant 1010 to the wax-resin continuous phase, and shear disperse at the third rotation speed and constant temperature to obtain a pre-dispersed wax material; S4: After obtaining the pre-dispersed wax material, adjust the stirring speed to the fourth speed, lower the system temperature, add the composite antioxidant and stir, then add the graded low-shrinkage organic filler phase in batches. After each batch of graded low-shrinkage organic filler phase is added, stir until there is no obvious dry powder agglomeration and large particle clumping before adding the material. After all the graded low-shrinkage organic filler phase has been added, continue to keep warm and stir. Then, perform vacuum degassing, and then perform coarse filtration through a stainless steel mesh to remove occasional large particle impurities and avoid retaining effective graded filler components. Finally, granulate and mold to obtain a special anti-denting molding material for large gas turbine casing molding.
[0007] As a preferred technical solution of the present invention, in step S1, the D50 particle size of the first low-ash organic support micro powder is 5-30 μm, for example, it can be 5 μm, 7.5 μm, 10 μm, 12.5 μm, 15 μm, 17.5 μm, 20 μm, 22.5 μm, 25 μm, 27.5 μm or 30 μm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0008] The first low-ash organic support micro powder is one or more of cross-linked polystyrene micro powder, cross-linked styrene-divinylbenzene copolymer micro powder, cross-linked polymethyl methacrylate micro powder, polyethylene micro powder or polypropylene micro powder; preferably cross-linked styrene-divinylbenzene copolymer micro powder or cross-linked polymethyl methacrylate micro powder.
[0009] In some optional embodiments, the vacuum drying temperature of the first low-ash organic support micropowder is 70-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0010] In some optional embodiments, the vacuum drying time of the first low-ash organic support micro powder is 2-4 hours, for example, it can be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0011] The number average molecular weight of the polyethylene wax is 2000-5000.
[0012] In some optional embodiments, the dropping point or softening point of the polyethylene wax is 90-120°C, for example, it can be 90°C, 93°C, 96°C, 99°C, 102°C, 105°C, 108°C, 111°C, 114°C, 117°C or 120°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0013] In some optional embodiments, the grafting rate of the maleic anhydride-grafted polyethylene wax is 0.5-3.0 wt.%, for example, it can be 0.5 wt.%, 0.75 wt.%, 1.0 wt.%, 1.25 wt.%, 1.5 wt.%, 1.75 wt.%, 2.0 wt.%, 2.25 wt.%, 2.5 wt.%, 2.75 wt.%, or 3.0 wt.%, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0014] In some optional embodiments, the mass ratio of the pretreated organic support micropowder, polyethylene wax, and maleic anhydride-grafted polyethylene wax is 1:(0.8-3):(0.2-1.2), for example, it can be 1:(0.8, 1.02, 1.24, 1.46, 1.68, 1.9, 2.12, 2.34, 2.56, 2.78 or 3):(0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1 or 1.2), but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0015] In some alternative embodiments, the shear mixing temperature is 105-130°C, for example, 105°C, 108°C, 111°C, 114°C, 117°C, 120°C, 123°C, 126°C, 128°C or 130°C, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0016] In some optional embodiments, when the polyethylene wax dropping point or softening point is ≤110°C, the shear mixing temperature is 105-120°C, and when the polyethylene wax dropping point or softening point is >110°C, the shear mixing temperature is 120-130°C.
[0017] In some alternative embodiments, the first rotational speed is 800-1800 rpm, for example, it can be 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1700 rpm or 1800 rpm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0018] In some optional embodiments, the shear mixing time is 30-60 min, for example, it can be 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0019] In some optional embodiments, the D50 particle size of the all-organic crystallized rheology modifier is 20-80 μm, for example, it can be 20 μm, 26 μm, 32 μm, 38 μm, 44 μm, 50 μm, 56 μm, 62 μm, 68 μm, 74 μm or 80 μm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0020] As a preferred technical solution of the present invention, in step S2, the mass ratio of 54#-60# fully refined paraffin wax to microcrystalline wax in the base wax phase is 1:(0.15-0.6), for example, it can be 1:0.15, 1:0.195, 1:0.24, 1:0.285, 1:0.33, 1:0.375, 1:0.42, 1:0.465, 1:0.51, 1:0.555 or 1:0.6, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0021] In some alternative embodiments, the temperature at which the base wax phase is stirred and melted is 85-100°C, for example, 85°C, 86.5°C, 88°C, 89.5°C, 91°C, 92.5°C, 94°C, 95.5°C, 97°C, 98.5°C, or 100°C, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0022] In some optional embodiments, the softening point of the resin reinforcing phase is 80-110°C, for example, it can be 80°C, 83°C, 86°C, 89°C, 92°C, 95°C, 98°C, 101°C, 104°C, 107°C or 110°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0023] The resin reinforcing phase is any one of hydrogenated rosin resin, hydrogenated terpene resin, or hydrogenated C5 petroleum resin. In some optional embodiments, the mass ratio of the base wax phase to the resin reinforcing phase is (40-55):(12-22), for example, it can be (40, 41.5, 43, 44.5, 46, 47.5, 49, 50.5, 52, 53.5 or 55):(12, 13, 14, 15, 16, 17, 18, 19, 20, 21 or 22), but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0024] In some optional embodiments, the temperature of the mechanical stirring is 100-120°C, for example, it can be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C or 120°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0025] In some alternative embodiments, the second rotational speed is 200-500 rpm, for example, it can be 200 rpm, 230 rpm, 260 rpm, 290 rpm, 320 rpm, 350 rpm, 380 rpm, 410 rpm, 440 rpm, 470 rpm or 500 rpm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0026] In some optional embodiments, the mechanical stirring time is 30-60 min, for example, it can be 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0027] As a preferred technical solution of the present invention, in step S3, the acid value of the anti-stratification stabilizer is 20-30 mgKOH / g, for example, it can be 20 mgKOH / g, 21 mgKOH / g, 22 mgKOH / g, 23 mgKOH / g, 24 mgKOH / g, 25 mgKOH / g, 26 mgKOH / g, 27 mgKOH / g, 28 mgKOH / g, 29 mgKOH / g or 30 mgKOH / g, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0028] In some optional embodiments, the third rotational speed is 800-1500 rpm, for example, it can be 800 rpm, 870 rpm, 940 rpm, 1010 rpm, 1080 rpm, 1150 rpm, 1220 rpm, 1290 rpm, 1360 rpm, 1430 rpm or 1500 rpm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0029] In some alternative embodiments, the shear dispersion temperature is 90-110°C, for example, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C or 110°C, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0030] In some optional embodiments, the shear dispersion time is 15-40 min, for example, it can be 15 min, 17.5 min, 20 min, 22.5 min, 25 min, 27.5 min, 30 min, 32.5 min, 35 min, 37.5 min or 40 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0031] In some optional embodiments, the mass ratio of the base wax phase, the all-organic crystallized rheology modifier, the anti-stratification stabilizer, and the antioxidant 1010 is (40-55):(1.5-5):(0.5-2):(0.1-0.5), for example, it can be (40, 41.5, 43, 44.5, 46, 47.5, 49, 50.5, 52, 53.5, or 55):(1.5, 1.85, 2.2, 2.55, 2.9, 3). 25, 3.6, 3.95, 4.3, 4.65 or 5: (0.5, 0.65, 0.8, 0.95, 1.1, 1.25, 1.4, 1.55, 1.7, 1.85 or 2): (0.1, 0.14, 0.18, 0.22, 0.26, 0.3, 0.34, 0.38, 0.42, 0.46 or 0.5), but not limited to the listed values; other unlisted values within this range also apply.
[0032] As a preferred technical solution of the present invention, in step S4, the fourth rotational speed is 200-600 rpm, for example, it can be 200 rpm, 240 rpm, 280 rpm, 320 rpm, 360 rpm, 400 rpm, 440 rpm, 480 rpm, 520 rpm, 560 rpm or 600 rpm, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0033] In some alternative embodiments, the pre-dispersed wax is cooled to 85-90°C, for example, 85°C, 85.5°C, 86°C, 86.5°C, 87°C, 87.5°C, 88°C, 88.5°C, 89°C, 89.5°C, or 90°C, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0034] In some optional embodiments, the stirring time after adding the composite antioxidant is 10-15 min, for example, it can be 10 min, 10.5 min, 11 min, 11.5 min, 12 min, 12.5 min, 13 min, 13.5 min, 14 min, 14.5 min or 15 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0035] In some optional embodiments, the mass ratio of antioxidant 1010 to antioxidant 168 in the composite antioxidant is 1:(1-2), for example, it can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0036] In some optional embodiments, the mass ratio of the base wax phase to the composite antioxidant is (40-55):(0.1-0.8), for example, it can be (40, 41.5, 43, 44.5, 46, 47.5, 49, 50.5, 52, 53.5 or 55):(0.1, 0.17, 0.24, 0.31, 0.38, 0.45, 0.52, 0.59, 0.66, 0.73 or 0.8), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0037] In some optional embodiments, the graded low-shrinkage organic filler phase is added in batches 2-4 times, for example, 2, 3 or 4 times, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0038] The graded low-shrinkage organic filler phase includes a second low-ash organic filler powder and a third low-ash organic filler powder; the D50 particle size of the second low-ash organic filler powder is 20-50 μm, for example, it can be 20 μm, 23 μm, 26 μm, 29 μm, 32 μm, 35 μm, 38 μm, 41 μm, 44 μm, 47 μm or 50 μm; the D50 particle size of the third low-ash organic filler powder is 60-120 μm, for example, it can be 60 μm, 66 μm, 72 μm, 78 μm, 84 μm, 90 μm, 96 μm, 102 μm, 108 μm, 114 μm or 120 μm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0039] The second low-ash organic filler powder and the third low-ash organic filler powder are each independently selected from one or more of cross-linked polystyrene powder, cross-linked styrene-divinylbenzene copolymer powder, or cross-linked polymethyl methacrylate powder; In some optional embodiments, the mass ratio of the second low-ash organic filler powder to the third low-ash organic filler powder is 1:(0.5-2), for example, it can be 1:0.5, 1:0.7, 1:0.9, 1:1.1, 1:1.3, 1:1.5, 1:1.7, 1:1.9 or 1:2, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0040] In some optional embodiments, the mass ratio of the base wax phase to the graded low-shrinkage organic filler phase is (40-55):(18-30), for example, it can be (40, 41.5, 43, 44.5, 46, 47.5, 49, 50.5, 52, 53.5 or 55):(18, 19.2, 20.4, 21.6, 22.8, 24, 25.2, 26.4, 27.6, 28.8 or 30), but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0041] In some optional embodiments, the stirring time after the addition of each batch of graded low-shrinkage organic filler phase is 10-15 min, for example, it can be 10 min, 10.5 min, 11 min, 11.5 min, 12 min, 12.5 min, 13 min, 13.5 min, 14 min, 14.5 min or 15 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0042] In some optional embodiments, the heat preservation and stirring time after the addition of all graded low-shrinkage organic filler phases is 20-60 min, for example, it can be 20 min, 24 min, 28 min, 32 min, 36 min, 40 min, 44 min, 48 min, 52 min, 56 min or 60 min, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0043] In some optional embodiments, the vacuum degree of the vacuum degassing is -0.09 to -0.06 MPa, for example, it can be -0.09 MPa, -0.087 MPa, -0.084 MPa, -0.081 MPa, -0.078 MPa, -0.075 MPa, -0.072 MPa, -0.069 MPa, -0.066 MPa, -0.063 MPa or -0.06 MPa, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0044] In some optional embodiments, the vacuum degassing time is 10-30 min, for example, it can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0045] In some optional embodiments, the aperture of the stainless steel mesh is 200-300μm, for example, it can be 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm or 300μm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0046] In some embodiments, the ash content of the resulting anti-dent special molding material for forming large gas turbine casings is not higher than 0.02 wt.%.
[0047] Secondly, the present invention provides a special anti-denting molding material for forming large gas turbine casings, which is prepared according to the preparation method described above.
[0048] The molding compound system of this invention addresses the problem of local depressions that easily occur in the thick-walled region of a large gas turbine casing during molding and cooling. Its effect does not come from the independent improvement of a single component, but from the combined effect of a continuous phase, a fully organic crystallized rheological composite modifier, a graded low-shrinkage organic filler phase, an anti-stratification stabilizer, and an antioxidant system.
[0049] The base wax phase and resin reinforcing phase constitute the continuous phase of the molding compound. Fully refined paraffin wax provides the basic fluidity required for injection molding, enabling the system to fill complex contours and thin rib areas. Microcrystalline wax helps improve the toughness and structural continuity of the wax phase, preventing the system from becoming excessively brittle during cooling. The resin reinforcing phase enhances the shape retention of the molding compound at room temperature and under certain thermal conditions, ensuring stable structural boundaries in the molded areas during subsequent cooling. This continuous phase provides a support for the remaining fusible organic functional components and influences the overall flow and molding state of the molding compound during transitions between liquid, semi-solid, and solid states.
[0050] In this system, the fully organic crystallized rheology modifier is mainly used to improve the interfacial wetting state and distribution stability of the organic support component in the wax-resin continuous phase, and can also participate in the regulation of the microstructure and rheological state during the cooling process of the wax phase. The first low-ash organic support micropowder has the characteristics of being flammable, low ash content, and fine-scale volumetric occupancy. When it is dispersed in the continuous phase with an appropriate particle size, it helps to form fine-scale organic support nodes during the liquid-solid transition stage, thereby reducing the tendency of the central shrinkage of thick-walled regions to concentrate and transfer to the surface. Unlike directly adding untreated organic support micropowder, in this application, the first low-ash organic support micropowder is first melt-sheared with polyethylene wax and maleic anhydride-grafted polyethylene wax to form a fully organic crystallized rheology modifier. Polyethylene wax exhibits good compatibility with the wax phase and can serve as a coating carrier and dispersion medium for organic-supported micropowders, making it easier for the organic-supported micropowders to be wetted by the continuous wax-resin phase when they enter. Maleic anhydride-grafted polyethylene wax helps improve the interfacial wetting and coating stability between the organic-supported micropowders and the continuous phase, reducing the agglomeration and sedimentation tendencies of fine-particle organic powders in non-polar systems. Pre-coating the organic support component before it enters the system helps reduce the agglomeration and sedimentation tendencies that may occur when the organic-supported micropowders are directly added, thereby improving the stability of its dispersion.
[0051] Besides the fine-scale organic support effect, the polyethylene wax and grafted polyethylene wax in the all-organic crystallized rheology modifier may also participate in the microstructure regulation during the wax phase cooling process and affect the rheological state in the semi-solid stage. The wax-resin continuous phase undergoes a transition from a fully fluid state to a semi-solid slurry state and then back to a solid state during temperature decrease. If the semi-solid stability of the system is insufficient during this stage, subsequent volume changes in the central part of the thick-walled region may be more easily transmitted to the surface through flow or traction. After the all-organic crystallized rheology modifier is dispersed in the continuous phase, it can regulate the local microstructure formation during the wax phase cooling process through the volume occupation of the first low-ash organic support micropowder, the compatibility transition between the polyethylene wax segments and the wax phase, and the interfacial wetting effect of the maleic anhydride grafted polyethylene wax. This helps to regulate the rheological state of the molding material in the liquid-solid transition range, improving its ability to maintain its morphology in the semi-solid stage. This support does not completely prevent shrinkage, but rather helps to make the shrinkage transmission process more moderate, thereby reducing the tendency for a certain local area to be subjected to concentrated traction.
[0052] Graded low-shrinkage organic filler phases primarily serve a fine volume compensation function. Dispersed in a relatively stable particulate form within the system, these phases act as a burnable volume-filling component within the continuous phase, helping to reduce the effective shrinkage of the mold material dominated by the continuous phase during cooling. Compared to single coarse-particle fillers, using a second and third low-ash organic filler powder for particle size gradation is beneficial for balancing volume compensation capability, filling of complex areas, and surface replication. The finer particle size component helps improve the replication properties of thin ribs and curved surfaces, while the larger particle size component helps provide volume filling and shrinkage buffering. In the semi-solid stage, this type of graded low-shrinkage organic filler phase may restrict local micro-region flow, helping to reduce the local migration tendency of the continuous phase in the later stages of cooling, thereby helping to reduce the tendency for shrinkage from the center of thick-walled regions to concentrate on the surface.
[0053] The role of anti-stratification stabilizers in this system is mainly reflected in improving interfacial wetting and suspension stability under all-organic conditions. Oxidized polyethylene wax with an acid value of 20-30 mg KOH / g combines polyethylene segments with moderately polar groups. On the one hand, it maintains compatibility with the wax phase; on the other hand, it helps improve the interfacial wetting state between the all-organic crystallization rheology modifier and the graded low-shrinkage organic filler phase and the continuous phase. This helps reduce secondary agglomeration between particles and the tendency for sedimentation and stratification caused by density differences during heat preservation, degassing, and settling, thereby improving the distribution consistency of organic support components and organic filler components in various parts of the product. For large wax molds such as large housings, this uniform distribution is one of the factors affecting the control of local depressions.
[0054] Antioxidant 1010 and the composite antioxidant are added at different stages: the addition of antioxidant 1010 in the early stage helps reduce the tendency of thermal oxidation changes in the wax-resin continuous phase and interfacial coating layer during the high-temperature shear dispersion stage; the addition of the composite antioxidant composed of antioxidant 1010 and antioxidant 168 in the later stage helps to further reduce the risk of thermal oxidation changes during the subsequent heat preservation, feeding, and degassing stages, thereby helping to maintain the relative stability of the system's viscosity, interfacial wetting state, and component dispersion state. This arrangement helps to reduce the impact of material state fluctuations during processing on the final molding consistency. At the same time, both antioxidant 1010 and antioxidant 168 are organic antioxidants, and their dosage is relatively low, which is beneficial to balancing the stability of mold material processing and the requirement of low ash loss on ignition.
[0055] Overall, the molding compound system of this invention exhibits a synergistic working mechanism of "all-organic rheological support - graded volume compensation - dispersion stability - low ash loss on ignition": the all-organic crystallized rheological composite modifier helps improve the wetting and distribution stability of fine-scale organic support components in the wax-resin continuous phase, and may participate in the semi-solid state regulation in the liquid-solid transition range; the graded low-shrinkage organic filler phase helps to compensate for the shrinkage of the continuous phase by volume occupation; the anti-delamination stabilizer helps to improve the distribution stability of the above two types of organic functional components in the high-filler system; the continuous phase and antioxidant system provide the basis for the fluidity, load-bearing capacity and processing stability of the molding compound processing and molding process.
[0056] Compared with the prior art, the beneficial effects of the present invention are as follows: This application does not employ a single volume compensation approach, but rather combines a fully organic crystallized rheological composite modifier (which improves the distribution stability of the organic supporting components and may regulate the morphological stability of the semi-solid stage) with a graded, low-shrinkage organic filler phase (fine volume occupation) in a continuous phase. This system helps improve the semi-solid stability of the fully organic, highly filled system in the liquid-solid transition region, and compensates for some shrinkage through fine-scale support and graded volume occupation, thereby reducing the tendency for post-shrinkage in the central region to concentrate and transfer to the pre-cured surface layer, and reducing the tendency for local depressions.
[0057] In this application, a first low-ash organic support micropowder is pre-formed into composite particles by melt shearing with polyethylene wax and maleic anhydride-grafted polyethylene wax. The polyethylene wax segments provide good compatibility with the base wax phase, while the maleic anhydride-grafted polyethylene wax improves the interfacial wetting state between the organic support micropowder and the continuous phase. This pre-coated structure helps reduce the agglomeration and sedimentation tendency of the fine-particle-size organic support component in the continuous phase; simultaneously, the polyethylene wax component is compatible with the wax phase and may participate in the microstructure regulation during the cooling stage, thereby improving the morphology retention ability of the molding compound in the semi-solid stage.
[0058] This application uses a graded low-shrinkage organic filler phase, combined with oxidized polyethylene wax as an anti-delamination stabilizer. The moderately polar groups of oxidized polyethylene wax help improve the interfacial wetting state between the graded low-shrinkage organic filler phase, the all-organic crystallized rheology modifier, and the wax-resin continuous phase. While maintaining a certain fluidity, it helps reduce the risk of density delamination and filler sedimentation of the molding compound during the heat preservation and vacuum degassing stages, while also balancing the integrity of thin-walled molding and the quality of surface reproduction. Attached Figure Description
[0059] Figure 1 This is a flowchart of the method for preparing the anti-denting special molding material for forming large gas turbine casings as described in this application; Figure 2The molded part is obtained by wax injection molding of the anti-dent special mold material for forming a large gas turbine casing prepared by the preparation method described in Example 1 of this application. Detailed Implementation
[0060] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include any obvious substitutions and modifications made to the embodiments described herein.
[0061] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone further purification or processing. Example 1
[0062] This embodiment provides a special anti-denting molding material for forming large gas turbine casings and its preparation method. The preparation method of the special anti-denting molding material for forming large gas turbine casings specifically includes the following steps: S1: Cross-linked styrene-divinylbenzene copolymer micropowder with a D50 of 20 μm was vacuum dried at 80 °C for 3 h to obtain pretreated organic support micropowder; the pretreated organic support micropowder, polyethylene wax with a number average molecular weight of 4000 and a dropping point of 110 °C, and maleic anhydride grafted polyethylene wax with a grafting rate of 2.0 wt.% were added to a high-shear mixing vessel at a mass ratio of 1:2.5:1.0; the temperature was raised to 120 °C, and shearing and mixing were performed at a first rotation speed of 1500 rpm for 50 min. After mixing, the material was spread in a thin layer on a stainless steel tray, pressed and solidified by a cooling roller, and then cryogenically pulverized and sieved to obtain a fully organic crystallized rheology modifier with a D50 of 70 μm; S2: The base wax phase (obtained by compounding 56# fully refined paraffin wax and microcrystalline wax at a mass ratio of 1:0.4) is added to the wax melting kettle and stirred and melted at 95°C; the resin reinforcing phase (hydrogenated rosin resin) with a softening point of 100°C is added, wherein the mass ratio of the base wax phase to the resin reinforcing phase is 50:18, the temperature is raised to 105°C, and the mixture is mechanically stirred at a second speed of 400 rpm for 50 min to obtain a continuous wax-resin phase; S3: Add an all-organic crystallization rheology modifier, an anti-stratification stabilizer (oxidized polyethylene wax with an acid value of 25 mg KOH / g) and antioxidant 1010 to the wax-resin continuous phase, and shear and disperse at 1200 rpm and 100°C for 30 min to obtain a pre-dispersed wax material, wherein the mass ratio of the base wax phase, the all-organic crystallization rheology modifier, the anti-stratification stabilizer and antioxidant 1010 is 50:3:1:0.3; S4: After obtaining the pre-dispersed wax, adjust the stirring speed to the fourth speed of 500 rpm, lower the system temperature to 88℃, add the composite antioxidant (antioxidant 1010 and antioxidant 168 are compounded at a mass ratio of 1:1.5) and stir for 12 min. The mass ratio of the base wax phase to the composite antioxidant is 50:0.5. Subsequently, a graded low-shrinkage organic filler phase is added in 3 batches. The graded low-shrinkage organic filler phase is composed of cross-linked styrene-divinylbenzene copolymer powder with a D50 of 35 μm and cross-linked polystyrene powder with a D50 of 90 μm. The mixture is prepared by mass ratio of 1:1, wherein the mass ratio of the base wax phase to the graded low-shrinkage organic filler phase is 50:25. After each batch of graded low-shrinkage organic filler phase is added, it is stirred for 12 minutes until there is no obvious dry powder agglomeration and large particle clumping before adding more material. After all the graded low-shrinkage organic filler phase is added, it is kept warm and stirred for another 50 minutes. Then, it is vacuum degassed for 25 minutes under a vacuum degree of -0.08MPa. After that, it is coarsely filtered through a stainless steel mesh with a pore size of 250μm, and then granulated to obtain a special anti-denting molding material for the molding of large gas turbine casings. Figure 2 The anti-dent special molding material for the large gas turbine casing is formed into a light green, semi-transparent waxy molded part after wax injection molding. The overall surface is relatively flat and has a slight waxy luster. No obvious delamination, cracks, black agglomeration spots or white filler-rich particles are observed, indicating that the fully organic crystallized rheology composite modifier and the graded low-shrinkage organic filler phase have good macroscopic dispersion uniformity in the wax-resin continuous phase. Example 2
[0063] This embodiment provides a special anti-denting molding material for forming large gas turbine casings and its preparation method. The preparation method of the special anti-denting molding material for forming large gas turbine casings specifically includes the following steps: S1: Cross-linked polymethyl methacrylate micropowder with a D50 of 30 μm was vacuum dried at 70 °C for 4 h to obtain pretreated organic support micropowder; the pretreated organic support micropowder, polyethylene wax with a number average molecular weight of 2000 and a dropping point of 90 °C, and maleic anhydride grafted polyethylene wax with a grafting rate of 0.5 wt.% were added to a high shear mixing vessel at a mass ratio of 1:0.8:0.2; the temperature was raised to 110 °C, and shearing and mixing were performed at a first rotation speed of 800 rpm for 30 min. After mixing, the material was spread in a thin layer on a stainless steel tray, pressed and solidified by a cooling roller, and then frozen, pulverized, and sieved to obtain a fully organic crystallized rheology modifier with a D50 of 20 μm; S2: The base wax phase (obtained by compounding 54# fully refined paraffin wax and microcrystalline wax at a mass ratio of 1:0.15) is added to the wax melting kettle and stirred and melted at 85°C; a resin reinforcing phase (hydrogenated terpene resin) with a softening point of 80°C is added, wherein the mass ratio of the base wax phase to the resin reinforcing phase is 40:22, the temperature is raised to 100°C, and the mixture is mechanically stirred at a second speed of 200 rpm for 30 min to obtain a continuous wax-resin phase; S3: Add an all-organic crystallization rheology modifier, an anti-stratification stabilizer (oxidized polyethylene wax with an acid value of 20 mg KOH / g), and antioxidant 1010 to the wax-resin continuous phase, and shear and disperse at 800 rpm and 90°C for 15 min to obtain a pre-dispersed wax material, wherein the mass ratio of the base wax phase, the all-organic crystallization rheology modifier, the anti-stratification stabilizer, and the antioxidant 1010 is 40:1.5:0.5:0.1; S4: After obtaining the pre-dispersed wax, adjust the stirring speed to the fourth speed of 200 rpm, lower the system temperature to 85℃, add the composite antioxidant (antioxidant 1010 and antioxidant 168 are compounded at a mass ratio of 1:1) and stir for 10 min. The mass ratio of the base wax phase to the composite antioxidant is 40:0.1. Then, add the graded low-shrinkage organic filler phase in two batches. The graded low-shrinkage organic filler phase consists of cross-linked styrene-divinylbenzene copolymer powder with a D50 of 20 μm and cross-linked polystyrene powder with a D50 of 60 μm, in a mass ratio of... The mixture is prepared by mixing the base wax phase and the graded low-shrinkage organic filler phase at a ratio of 1:0.5, with a mass ratio of 40:18. After each batch of graded low-shrinkage organic filler phase is added, the mixture is stirred for 10 minutes until there is no obvious dry powder agglomeration or large particle clumping before adding more material. After all the graded low-shrinkage organic filler phase has been added, the mixture is kept warm and stirred for another 20 minutes. Then, the mixture is vacuum degassed for 10 minutes at a vacuum degree of -0.06MPa. After that, it is coarsely filtered through a stainless steel mesh with a pore size of 200μm, and then granulated to obtain a special anti-denting molding material for the molding of large gas turbine casings. Example 3
[0064] This embodiment provides a special anti-denting molding material for forming large gas turbine casings and its preparation method. The preparation method of the special anti-denting molding material for forming large gas turbine casings specifically includes the following steps: S1: Cross-linked styrene-divinylbenzene copolymer micropowder with a D50 of 5 μm was vacuum dried at 90℃ for 2 h to obtain pretreated organic support micropowder; the pretreated organic support micropowder, polyethylene wax with a number average molecular weight of 3000 and a dropping point of 120℃, and maleic anhydride grafted polyethylene wax with a grafting rate of 1.0 wt.% were added to a high shear mixing vessel at a mass ratio of 1:1.5:0.5; the temperature was raised to 130℃, and shearing and mixing were performed at a first rotation speed of 1000 rpm for 40 min. After mixing, the material was spread in a thin layer on a stainless steel tray, pressed and solidified by a cooling roller, and then frozen, pulverized, and sieved to obtain a fully organic crystallized rheology modifier with a D50 of 50 μm; S2: The base wax phase (obtained by compounding 60# fully refined paraffin wax and microcrystalline wax at a mass ratio of 1:0.6) is added to the wax melting kettle and stirred and melted at 100°C; the resin reinforcing phase (hydrogenated C5 petroleum resin) with a softening point of 90°C is added, wherein the mass ratio of the base wax phase to the resin reinforcing phase is 55:12, the temperature is raised to 120°C, and the mixture is mechanically stirred at a second speed of 500 rpm for 60 min to obtain a continuous wax-resin phase; S3: Add an all-organic crystallization rheology modifier, an anti-stratification stabilizer (oxidized polyethylene wax with an acid value of 30 mg KOH / g) and antioxidant 1010 to the wax-resin continuous phase, and shear and disperse at 1500 rpm and 110°C for 40 min to obtain a pre-dispersed wax material, wherein the mass ratio of the base wax phase, the all-organic crystallization rheology modifier, the anti-stratification stabilizer and antioxidant 1010 is 55:5:2:0.5; S4: After obtaining the pre-dispersed wax, adjust the stirring speed to the fourth speed of 600 rpm, lower the system temperature to 90℃, add the composite antioxidant (antioxidant 1010 and antioxidant 168 are compounded at a mass ratio of 1:2) and stir for 15 min. The mass ratio of the base wax phase to the composite antioxidant is 55:0.8. Subsequently, a graded low-shrinkage organic filler phase is added in 4 batches. The graded low-shrinkage organic filler phase consists of cross-linked polymethyl methacrylate powder with a D50 of 50 μm and cross-linked polystyrene powder with a D50 of 120 μm, in a mass ratio of... The mixture is prepared by blending the base wax phase and the graded low-shrinkage organic filler phase at a ratio of 1:2, with a mass ratio of 55:30. After each batch of graded low-shrinkage organic filler phase is added, the mixture is stirred for 15 minutes until there is no obvious dry powder agglomeration or large particle clumping before adding more material. After all the graded low-shrinkage organic filler phase has been added, the mixture is kept warm and stirred for another 60 minutes. Then, the mixture is vacuum degassed for 30 minutes at a vacuum degree of -0.09MPa. After that, it is coarsely filtered through a stainless steel mesh with a pore size of 300μm, and then granulated to obtain a special anti-denting molding material for the molding of large gas turbine casings. Example 4
[0065] This embodiment provides a special anti-denting molding material for forming large gas turbine casings and its preparation method. The preparation method of the special anti-denting molding material for forming large gas turbine casings specifically includes the following steps: S1: Cross-linked polystyrene micro powder with a D50 of 10 μm was vacuum dried at 80 °C for 3.5 h to obtain pretreated organic support micro powder; the pretreated organic support micro powder, polyethylene wax with a number average molecular weight of 5000 and a dropping point of 100 °C, and maleic anhydride grafted polyethylene wax with a grafting rate of 3.0 wt.% were added to a high shear mixing vessel at a mass ratio of 1:3:1.2; the temperature was raised to 115 °C, and shearing and mixing were performed at a first rotation speed of 1800 rpm for 60 min. After mixing, the material was spread in a thin layer on a stainless steel tray, pressed and solidified by a cooling roller, and then frozen, pulverized, and sieved to obtain a fully organic crystallized rheology modifier with a D50 of 80 μm; S2: The base wax phase (obtained by compounding 58# fully refined paraffin wax and microcrystalline wax at a mass ratio of 1:0.3) is added to the wax melting kettle and stirred and melted at 90°C; the resin reinforcing phase (hydrogenated rosin resin) with a softening point of 110°C is added, wherein the mass ratio of the base wax phase to the resin reinforcing phase is 45:20, the temperature is raised to 115°C, and the mixture is mechanically stirred at a second speed of 300 rpm for 40 min to obtain a continuous wax-resin phase; S3: Add an all-organic crystallization rheology modifier, an anti-stratification stabilizer (oxidized polyethylene wax with an acid value of 22 mg KOH / g) and antioxidant 1010 to the wax-resin continuous phase, and shear and disperse at 1000 rpm and 95°C for 25 min to obtain a pre-dispersed wax material, wherein the mass ratio of the base wax phase, the all-organic crystallization rheology modifier, the anti-stratification stabilizer and antioxidant 1010 is 45:4:1.5:0.4; S4: After obtaining the pre-dispersed wax, adjust the stirring speed to the fourth speed of 400 rpm, lower the system temperature to 86℃, add the composite antioxidant (antioxidant 1010 and antioxidant 168 are compounded at a mass ratio of 1:1.8) and stir for 14 min. The mass ratio of the base wax phase to the composite antioxidant is 45:0.6. Then, add the graded low-shrinkage organic filler phase in 3 batches. The graded low-shrinkage organic filler phase consists of cross-linked styrene-divinylbenzene copolymer powder with a D50 of 40 μm and cross-linked polymethyl methacrylate powder with a D50 of 80 μm. The mixture was prepared by mixing the base wax phase and the graded low-shrinkage organic filler phase at a mass ratio of 1:1.2, with a mass ratio of 45:22. After each batch of graded low-shrinkage organic filler phase was added, the mixture was stirred for 14 minutes until there was no obvious dry powder agglomeration or large particle clumping before adding more material. After all the graded low-shrinkage organic filler phase was added, the mixture was kept warm and stirred for another 40 minutes. Then, the mixture was vacuum degassed for 15 minutes at a vacuum degree of -0.07MPa. After that, it was coarsely filtered through a stainless steel mesh with a pore size of 280μm, and then granulated to obtain a special anti-denting molding material for the molding of large gas turbine casings.
[0066] Comparative Example 1 This comparative example provides a special anti-denting molding material for forming large gas turbine casings and its preparation method. The difference from Example 1 is that the fully organic crystallized rheology modifier is omitted in S1 and S3, and the amount of fully organic crystallized rheology modifier is made up with an equal mass of base wax phase. Other operating steps and process parameters are exactly the same as in Example 1.
[0067] Comparative Example 2 This comparative example provides a special anti-dent molding material for forming large gas turbine casings and its preparation method. The difference from Example 1 is that the melt pre-coating preparation process in S1 is omitted. Instead, in S3, the pretreated organic support micropowder, polyethylene wax and maleic anhydride grafted polyethylene wax are directly added in the same mass ratio and total amount as the first low ash organic support micropowder, polyethylene wax and maleic anhydride grafted polyethylene wax contained in the all-organic crystallized rheology composite modifier in Example 1. Other operating steps and process parameters are exactly the same as in Example 1.
[0068] Comparative Example 3 This comparative example provides a special anti-denting molding material for forming large gas turbine casings and its preparation method. The difference from Example 1 is that no anti-delamination stabilizer is added in S3, and the amount of anti-delamination stabilizer is made up with an equal mass of base wax phase. Other operating steps and process parameters are exactly the same as in Example 1.
[0069] Comparative Example 4 This comparative example provides a special anti-denting molding material for forming large gas turbine casings and its preparation method. The difference from Example 1 is that in S4, the graded low-shrinkage organic filler phase is replaced with an equal mass of conventional single coarse-grained cross-linked polystyrene powder (D50 is 150 μm). Other operating steps and process parameters are exactly the same as in Example 1.
[0070] The performance of the anti-denting special molding materials for forming large gas turbine casings in Examples 1-4 and Comparative Examples 1-4 was tested, and the specific process is as follows: The mold materials obtained from each embodiment and comparative example were used to prepare standard test samples using the same industrial wax injection machine under the same process parameters (wax injection temperature 80℃, wax injection pressure 2.0MPa, holding time 60s). After the samples were allowed to stand at room temperature (25℃±1℃) for 24 hours to equilibrate, the following tests were conducted: Thick-walled dent resistance test: Thick-walled test blocks were cast using a cubic thick-walled steel mold with cavity dimensions of 50mm×50mm×50mm. After the test blocks had completely cooled, demolded, and reached temperature equilibrium, a coordinate measuring machine was used to scan the upper surface of the test block (i.e., the side opposite the wax injection port), and the maximum dent depth (mm) of the central area relative to the edge plane was measured. The smaller this value, the stronger the mold material's ability to resist the shrinkage pull of the internal thick wall.
[0071] Suspension stability test: Each group of mold materials was heated to 85℃ until completely melted and stirred evenly. The melted mixture was then poured into graduated glass test tubes with an inner diameter of 20mm and a height of 150mm. The tubes were placed in an 85℃ constant temperature oven and kept at that temperature for 4 hours. Afterward, the tubes were removed and allowed to cool naturally to room temperature for curing. The test tubes were broken open, and sections 20mm below the top and 20mm above the bottom of the cylindrical mold material were cut. The density of the top and bottom samples was measured using Archimedes' displacement method, and the density difference (g / cm³) was calculated. 3 The smaller the density difference, the better the anti-sedimentation and suspension stability of the fully organic crystallized rheology composite modifier and the graded low-shrinkage organic filler phase in the system.
[0072] Thin-walled filling integrity test: A standard Archimedes spiral mold (with a semi-circular groove cross-section, 1.5 mm in both depth and width) was used to test the filling capacity of the mold material. The mold material was injected into the mold under the same wax injection parameters. After demolding, the continuous filling length (mm) of the spiral wax mold was measured. A longer filling length indicates that the mold material, even with a large amount of organic filler, still possesses good fluidity and adaptability to molding complex thin-rib areas.
[0073] Surface copying performance (roughness) test: Under constant temperature and humidity conditions, take the smooth side surface of the Archimedes spiral wax pattern or thick-walled specimen prepared above, and use a stylus-type surface roughness measuring instrument to measure the arithmetic mean deviation Ra (μm) of the surface profile along the direction perpendicular to the filling flow. Five points are randomly selected for each sample for measurement, and the average value is taken. This index is used to evaluate the influence of mold material components (especially the particle size distribution and dispersion state of organic powder) on the surface smoothness of the wax pattern.
[0074] The test results are shown in Table 1.
[0075] Table 1: Performance test results of anti-denting special molding materials for forming large gas turbine casings in Examples 1-4 and Comparative Examples 1-4
[0076] As can be seen from the test results of Example 1 and Comparative Example 1 in Table 1, without the addition of the fully organic crystallized rheology composite modifier, the pre-coated organic support micro powder, polyethylene wax and maleic anhydride grafted polyethylene wax lack the regulating effect on the semi-solid state in the liquid-solid transition stage, and also lack the buffering effect of fine-scale organic support nodes on the shrinkage transmission of thick-walled areas. This makes it easier for the center of the thick-walled specimen to transfer to the previously solidified surface layer during the cooling process, thus increasing the maximum indentation depth of the thick wall. Since the system does not contain this composite modifier, the melt flow resistance is relatively low, the thin-wall filling length is increased, and the surface roughness is also kept at a low level.
[0077] As can be seen from the test results of Example 1 and Comparative Example 2 in Table 1, without the melt pre-coating treatment of S1, the first low-ash organic support micropowder, polyethylene wax, and maleic anhydride-grafted polyethylene wax were directly added to the wax-resin continuous phase. The interfacial wetting and coating stabilizing effects formed by the polyethylene wax and maleic anhydride-grafted polyethylene wax during the pre-coating process were lacking. The fine-particle-size organic support micropowder was more prone to local agglomeration in the high-filled wax-based system, which increased the local flow resistance and led to the decrease in thin-wall filling length. The organic support micropowder with insufficient dispersion stability was more prone to migration, local enrichment, or uneven distribution during the standing and degassing process, which led to an increase in the standing density difference. Due to the decrease in the spatial distribution uniformity of the composite regulator, it was difficult to give full play to the semi-solid state regulation and shrinkage transfer buffering effect, which reduced the thick-wall anti-dent ability and increased the maximum dent depth. In addition, the agglomerated particles were more likely to form local rough points or micro-contour fluctuations at the mold wall, which led to an increase in surface roughness.
[0078] As shown in Table 1, the test results of Example 1 and Comparative Example 3 indicate that without the addition of an anti-stratification stabilizer, the moderate polar groups and polyethylene segments in the oxidized polyethylene wax lack the regulating effect on the interfacial wetting and dispersion stability of the all-organic filler. This leads to the all-organic crystallization rheology composite modifier and the graded low-shrinkage organic filler phase being more prone to longitudinal migration and sedimentation during the degassing and static heat preservation stages, resulting in an increased static density difference. The increased density distribution difference within the material affects the consistency of the shrinkage state of various parts of the wax mold and the uniformity of the distribution of organic functional components. The insufficient local volume compensation effect leads to a larger maximum indentation depth in thick walls. In addition, the uneven distribution of components may increase the local viscosity fluctuation of the melt when it flows at the front edge, hindering the filling process and causing a decrease in the thin-wall filling length. At the same time, the locally enriched filler may also lead to an increase in surface roughness.
[0079] As shown in Table 1, the test results of Example 1 and Comparative Example 4 indicate that replacing the graded low-shrinkage organic filler with conventional single coarse-grained powder, although the coarse particles can still provide a certain volume occupation and shrinkage compensation effect, so that the maximum indentation depth of the thick wall only deteriorates to a certain extent and the static density difference does not increase significantly, the excessively large particle size weakens the fine filling ability of the system. The coarse particles are more likely to produce mechanical interference or local "bridging" phenomenon when flowing through the thin-walled ribs and complex transition corners, resulting in a shortening of the thin-walled filling length. At the same time, due to the excessively coarse powder particle size, it is easier to form local rough points or micro-contour fluctuations on the surface of the wax model after demolding, which weakens the surface copying ability and leads to an increase in surface roughness.
[0080] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A special anti-denting molding material for forming large gas turbine casings, characterized in that, It includes a base wax phase, a resin-reinforcing phase, a fully organic crystallized rheology modifier, an anti-stratification stabilizer, antioxidant 1010, a composite antioxidant, and a graded low-shrinkage organic filler phase; among which: The all-organic crystallized rheology composite modifier is prepared from a first low-ash organic supporting micro powder, polyethylene wax, and maleic anhydride-grafted polyethylene wax. The anti-delamination stabilizer is oxidized polyethylene wax with an acid value of 20-30 mg KOH / g; The graded low-shrinkage organic filler phase is a combination of a second low-ash organic filler powder and a third low-ash organic filler powder. The D50 of the second low-ash organic filler powder is 20-50 μm, and the D50 of the third low-ash organic filler powder is 60-120 μm. The mass ratio of the second low-ash organic filler powder to the third low-ash organic filler powder is 1:(0.5-2). The second low-ash organic filler powder and the third low-ash organic filler powder are each independently selected from one or more of cross-linked polystyrene powder, cross-linked styrene-divinylbenzene copolymer powder, or cross-linked polymethyl methacrylate powder. The first low-ash organic-supported micro powder has a D50 of 5-30 μm and an ash content of no more than 0.02 wt.%. The first low-ash organic support micro powder is one or more of the following: cross-linked polystyrene micro powder, cross-linked styrene-divinylbenzene copolymer micro powder, cross-linked polymethyl methacrylate micro powder, polyethylene micro powder, or polypropylene micro powder; The polyethylene wax has a number-average molecular weight of 2000-5000 and a dropping point or softening point of 90-120℃. The grafting rate of the maleic anhydride-grafted polyethylene wax is 0.5-3.0 wt.%. The mass ratio of the base wax phase to the resin-reinforced phase is (40-55):(12-22); The mass ratio of the basic wax phase, the all-organic crystallized rheology composite modifier, the anti-stratification stabilizer, and the antioxidant 1010 is (40-55):(1.5-5):(0.5-2):(0.1-0.5); The mass ratio of the base wax phase to the composite antioxidant is (40-55):(0.1-0.8); The mass ratio of the base wax phase to the graded low-shrinkage organic filler phase is (40-55):(18-30).
2. The anti-denting special molding material for forming large gas turbine casings according to claim 1, characterized in that: The base wax phase is obtained by compounding 54#-60# fully refined paraffin wax and microcrystalline wax at a mass ratio of 1:(0.15-0.6); The resin reinforcing phase is hydrogenated rosin resin, hydrogenated terpene resin, or hydrogenated C5 petroleum resin with a softening point of 80-110℃.
3. The anti-denting special molding material for forming large gas turbine casings according to claim 1, characterized in that: The composite antioxidant is obtained by compounding antioxidant 1010 and antioxidant 168 in a mass ratio of 1:(1-2).
4. The method for preparing the anti-denting special molding material for forming large gas turbine casings according to any one of claims 1-3, characterized in that, The preparation method includes: S1: After pretreatment of the first low-ash organic support micro powder, it is mixed with polyethylene wax and maleic anhydride grafted polyethylene wax, and then subjected to melt shearing, cooling solidification, crushing and sieving to obtain a fully organic crystallized rheology composite modifier. S2: After melting the base wax phase, add the resin reinforcing phase and mix to obtain a continuous wax-resin phase; S3: Add the all-organic crystallization rheology composite modifier, anti-stratification stabilizer and antioxidant 1010 to the wax-resin continuous phase, and shear and disperse to obtain a pre-dispersed wax material; S4: After slowing down and cooling the pre-dispersed wax material, add the composite antioxidant and stir. Then add the graded low-shrinkage organic filler phase in batches. After keeping warm and stirring, perform vacuum degassing, coarse filtration, and granulation to obtain a special anti-denting mold material for forming large gas turbine casings.
5. The method for preparing the anti-denting special molding material for forming large gas turbine casings according to claim 4, characterized in that, In S1: The pretreatment process is as follows: the first low-ash organic support micro powder is vacuum dried at 70-90℃ for 2-4 hours to obtain pretreated organic support micro powder; The mixing and shearing process is as follows: the pretreated organic support micro powder, polyethylene wax and maleic anhydride grafted polyethylene wax are added into a high shear mixing vessel at a mass ratio of 1:(0.8-3):(0.2-1.2), and sheared and mixed at 105-130℃ and 800-1800rpm for 30-60min. The D50 of the fully organic crystallized rheology modifier after sieving is 20-80 μm.
6. The method for preparing the anti-denting special molding material for forming large gas turbine casings according to claim 4, characterized in that, In S2: The base wax phase is added to a wax melting vessel and stirred and melted at 85-100℃; after adding the resin reinforcing phase, the temperature is raised to 100-120℃ and mechanically stirred at 200-500 rpm for 30-60 minutes.
7. The method for preparing the anti-denting special molding material for forming large gas turbine casings according to claim 4, characterized in that, In S3: The shear dispersion is carried out at a temperature of 90-110℃, a rotation speed of 800-1500rpm, and a time of 15-40min.
8. The method for preparing the anti-denting special molding material for forming large gas turbine casings according to claim 4, characterized in that, In S4: Adjust the stirring speed to 200-600 rpm, and after the system temperature drops to 85-90℃, add the composite antioxidant and stir for 10-15 minutes. The graded low-shrinkage organic filler phase is added in 2-4 batches, and stirred for 10-15 minutes after each batch is added. After all the batches are added, continue stirring at the temperature for 20-60 minutes.
Citation Information
Patent Citations
Investment precision casting pattern material for accessory casting and preparation method of investment precision casting pattern material
CN113182488A
Special model wax for high-temperature alloy and preparation method thereof
CN119431999A